2006
DOI: 10.1017/s1742758406415691
|View full text |Cite
|
Sign up to set email alerts
|

Participatory evaluation of synthetic and botanical pesticide mixtures for cotton bollworm control

Abstract: Abstract. The bioefficacy of various plant extracts, namely Azadirachta indica A. Juss, Khaya senegalensis Desrousseaux (A. Jussieu) and Hyptis suavuolens (L.) Poit, either alone or in combination with half the recommended dose of synthetic pesticides, was studied with farmers to find a more sustainable strategy for the management of bollworms in cotton. A number of treatments were farmer innovations. The treatments were compared six times during the season to the application of the fully recommended dose of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Earlier authors reported that neem seed extract (6 kg/ha) were most effective in reducing bollworm incidence and damage, and produced the highest yields of cottonseed (Sinzogan et al 2006). The aqueous seed extracts of Azadirachta indica were applied at the rate of 30, 50, 75 and 100 g/l to control S. derogata and reported high fruit yield of okra plant in Ghana (Obeng-Ofori 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier authors reported that neem seed extract (6 kg/ha) were most effective in reducing bollworm incidence and damage, and produced the highest yields of cottonseed (Sinzogan et al 2006). The aqueous seed extracts of Azadirachta indica were applied at the rate of 30, 50, 75 and 100 g/l to control S. derogata and reported high fruit yield of okra plant in Ghana (Obeng-Ofori 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Juss., pignut = Hyptis suaveolens (L.) Poit.] provided greater efficacy than the conventional products alone at their recommended rate 10. None of the plant extracts alone provided adequate crop protection.…”
Section: Less Developed (‘Poor’) Countriesmentioning
confidence: 99%
“…In a study of damage to cotton by the bollworm (Helicoverpa armigera H¨ubner) in Benin, it was reported that mixtures of extracts of three local plants Azadirachta indica, Khaya senegalensis, Hyptis suaveolens provided greater efficacy than the conventional inorganic products at their recommended rate (Sinzogan et al,2006). The incidence and severity of virus diseases is considered to be directly related with availability and abundance of insect vector and depend upon the time of infection (Dhingra and Ghosh, 1993).…”
Section: Discussionmentioning
confidence: 99%